Pengaruh Transfer Pricing terhadap Laporan Keuangan dan Pembebanan Pajak pada Perusahaan Afiliasi (Studi Kasus Pada PT X Indonesia) Tahun Buku 2019 - Fahira, Hilza; Wiyono, Slamet (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This study aims to analyze the impact of transfer pricing policies on financial statements and tax charges in affiliated companies, using a case study on PT X Indonesia in 2019. The research employs a descriptive qualitative method with a case study approach, supported by secondary data such as financial statements and transfer pricing documentation. The findings indicate that the implementation of transfer pricing for affiliated services did not result in aggressive profit or tax shifting but instead contributed to increased efficiency and company profitability. The use of the Transactional Net Margin Method (TNMM) and benchmarking analysis shows that the company’s margin ratios remain within an acceptable arm’s length range. Furthermore, the availability of complete documentation and benefit tests for management services demonstrates compliance with the Arm’s Length Principle. Therefore, the transfer pricing policy is fiscally acceptable and does not lead to significant tax corrections by the authorities.